Personality’s Financial and Psychological Footprint: Exploring the Interplay Between Financial Independence, Credit Card Debt, and Subjective Well- Being in Emerging Adults - Yu Zhang (Journal of Financial Therapy, 2026)
As emerging adults attain financial independence, it is essential to investigate their subjective well-being from psychological and financial perspectives. This study constructs and validates a conceptual model, informed by self-determination theory, to examine the relationships among personality traits, financial independence, credit card use, and subjective well-being in emerging adults. The findings reveal that all five personality traits are significantly linked to subjective well-being; however, neuroticism is the only trait with a negative correlation. Highly conscientious individuals tend to achieve greater financial independence. Highly neurotic individuals are more likely to maintain unpaid balances on credit or store cards. Additionally, financial independence and the tendency to carry credit card balances are positively correlated among emerging adults. Individuals exhibiting conscientiousness are positively and indirectly associated with outstanding credit card balances, emphasizing the intervening role of financial independence. Interestingly, neither financial independence nor credit card debt behavior has a significant association with subjective well-being. Subgroup analyses were also conducted based on gender, race, and college educational experience, revealing similarities and differences from the results observed in the full sample.
Keywords: credit card; emerging adult; personality; subjective well-being